Multi-omics analysis reveals inhibition of osteosarcoma progression by sporoderm-removed Ganoderma lucidum spores via targeting glycerophospholipid and fatty acid metabolism - Haitao Pan; Congshu Li; Mengyao Wang; Kang Ye; Xiaohui Fan; Yongping Fu; Jihong Yang; Zhenhao Li (Scientific Reports)
Abstract Osteosarcoma (OS) is a severe malignancy affecting children and adolescents, with limited effective treatments leading to poor outcomes. This study explored the potential of sporoderm-removed Ganoderma lucidum spores (RGLS) as a novel therapeutic agent against OS and elucidated its mechanism of action. Our in vivo and in vitro experiments showed that RGLS significantly inhibited S-180 OS cell proliferation, while simultaneously inducing apoptosis. Multi-omics analysis revealed that RGLS disrupted glycerophospholipid metabolism by upregulating lysophosphatidylcholine (LysoPC) levels through phospholipase A2 (PLA2)-mediated pathways. Co-culture assays further demonstrated that RGLS promoted the endocytosis of macrophage-derived Pla2g7 protein into S-180 cells, enhancing its anti-cancer effects. Additionally, RGLS modulated the cellular fatty acid profile and suppressed the β-oxidation of long-chain fatty acids, leading to energy depletion in OS cells. These findings provide a novel view of the multi-targeted mechanisms of RGLS, positioning it as a promising candidate for OS therapy.